Padrões emergentes em relações sistêmicas numa comunidade de fanfictions: oportunidades de aprendizagem no contexto da Língua Portuguesa - Anderson Nunes Rocha (2024)
This research aims to investigate the practices of fanfictions (fictions created by fans) within the scope of a specific fictional community, seeking to identify their peculiarities from the perspective of complexity theory and contributions to learning the Portuguese language. Fictional texts are created by fans based on the objects of their adoration, on a non-profit basis, which make use of characters or fictional universes from literature, cinema, comics, among other media. This practice, wether using pedagogical purpose, finds resonance in the curricular parameters of high school, since language is considered a human capacity to articulate collective meanings, sharing them in arbitrary representation systems that vary according their needs and social experiences. In this case, experiences of community interactions. The research aims, therefore, to identify how the themes addressed in fictional productions on a specific fanfiction platform can create emerging patterns based on the conditions of the Complex emergency. Complexity, according to Morin (2015), is defined as a tissue of heterogeneous constituents inseparably associated, being the set of events, actions, interactions, feedback, determinations and coincidences that constitute the phenomenal world. Thefore, a bibliographic survey was carried out on fanfiction studies from the perspective of complexity, it was noticeable the scarcity of researches in this area and its relevance for learning the Portuguese language. In this context, this study seeks to answer the following guiding questions: what are the emerging recursive dynamics resulting from literate practices in fanfictions that are part of practitioners' daily lives? How can systemic relationships in a fanfiction community influence the literate expressiveness of practitioners? How are the recurring elements and factors observed in fanfictions transposed to other environments that promote learning the Portuguese language? To this end, an online platform for fictional practices was selected, and the methodology involved bibliographical research and qualitative field research, with data collection through questionnaires and interviews with participants about their experiences on the fanfiction platform. The theoretical basis is based on the contributions of authors who discuss complexity theory, fanfiction communities and learning the Portuguese language. It was found that the systemic relationships developed through fanfiction practices can create opportunities for learning the Portuguese language, since they have the capacity to create social engagement.